TRENDS IN THE FUNCTIONING OF THE TOURISM SECTOR IN CRISIS CONDITIONS ON THE EXAMPLE OF HOTEL ENTERPRISES OF THE TRANSCARPATHIAN REGION, UKRAINE - Vitalia Chyniak; Maryana Salyuk (Economics & Education, 2022)
The purpose of the article is to identify trends in the operation of hotels in the Transcarpathian region in the pre-pandemic and pandemic periods, based on the ratio of the indicators of the dynamics of tourist flows and the occupancy rate of enterprises. It is obvious that small hotel enterprises of Transcarpathian region make a significant part of the hospitality segment of the region – they are the ones who receive a large part of guests/visitors/tourists. The activities of most of them are diversified, small-scale and somewhat isolated, these factors have softened the impact of strict quarantine restrictions introduced at different times in 2020-2021. Therefore, the research methodology is based on a sample of questionnaires – interviews provided by 30 enterprises. The research was conducted in the period from January to April 2021, when the restrictions of the red quarantine zone were introduced in the Transcarpathian region of Ukraine during the COVID-19 pandemic. In addition, a literature review of scientific works of domestic and foreign authors was conducted, whose publications relate to some aspects of this research. Much of the research concerns the state and current functioning of the tourism or hospitality industry during the pandemic and the business innovations they employ during the crisis. The results of the survey reflect the highly indicative dynamics of tourist flows in the Transcarpathian region in the period 2000-2020, showing pronounced peaks in the number of visitors (2000, 2003, 2008) and their decline (2001, 2004, 2019), as well as periods of low tourist activity (2014-2016) due to the military and political situation in Ukraine. The study describes the occupancy trends of small and medium-sized hotels in the region for the period 2018-2020. These trends clearly show the consequences of the crisis phenomena that occurred in the economy and society due to the global pandemic. The practical implications of the study lie in possible further recommendations for management decisions that will allow to increase the competitiveness of the hospitality and tourism sector in the region, as well as to implement effective measures in possible crisis situations. Value/originality. Information about the reaction and details of the operation of hotel enterprises of the Transcarpathian region during the global pandemic crisis is useful for understanding the work of the tourism sector in general at different levels – from local to state.